Chinese Consumers' E-Learning Satisfaction and Continuance Purchase Intention on Paid Online Python Course - Zhang, Jingjing; She, Long; Wang, Dongyuan; Shafiq, Ali (Frontiers in Psychology, 2022)
With the development of the internet technology, e-learning become an important part of the modern education system and the e-learning market faces huge competition. Consumers’ continuance purchase intention became one of the factors that decides the success of e-learning course and organization. Thus, factors that influence consumers’ continuance purchase intention seems should be considered in the e-learning market. However, little research focuses on identifying the process of continuance purchase intention of e-learning course. Based on the Information System Continuity Model, this paper develops a research model to investigate the factors that influence satisfaction and continuance purchase intention on e-learning. The cross-sectional, questionnaire-based research designed used in this study. Data collected from the consumers who enrolled in paid online python course. In total, 508 consumers who enrolled in paid online python course completed the online survey. The SmartPLS software were used for data analysis. The results demonstrate that perceived course quality, service quality, convenience and usefulness are significantly affect consumers’ satisfaction with the experience course. Moreover, the findings show that satisfaction, self-efficacy and e-word of mouth decide the consumers’ continuance purchase intention of the reminder course. The implications for theory and practice and future research directions are discussed.